Sago Palm (Metroxylon sagu Rottb.): Now and Beyond - Chung, Hung Hui; Mohd Hasnain, Bin Md Hussain; Kopli, Bin Bujang; Whye, Leonard Kit Lim (Universiti Putra Malaysia Press, 2019)
The sago palm (Metroxylon sagu Rottb.) is one of the underutilized food crops that has the promising potential to strengthen food security program especially in Sarawak, Malaysia. Thriving well in harsh environments such as the freshwater swampy area, the sago palm is also unique for its ability to store starch within its trunk, compared to other types of starch storage organs. With its superb high starch yield as compared to commonly found starch sources such as the corn, rice and wheat, it is deemed as the palm of many uses. Researches sprouting from this unique palm come from various fields of study, namely microbiology, food technology, polymer synthesis, bioprocess technology and most recently, computational biology. In this review, we presented a survey of recently published results from each field and further provided future recommendations and knowledge gaps to be filled. It is hoped that with the consolidation of research talents and funding from around the world, the sago palm industry will be matured in time to equip mankind with the solutions to combat the oncoming global food scarcity issues.